Differences in the attitudes to sport psychology consulting between individual and team sport athletes - Rooney, D.; Jackson, R. C.; Heron, N. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background The purpose of the present study was to investigate how an athlete`s participation in either an individual or team sport is related to their attitude toward sport psychology consulting and their willingness to consult a sport psychology practitioner.